PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN MINAT BELAJAR PADA MATA PELAJARAN IPS SISWA KELAS V MADRASAH IBTIDAIYAH DARUL ULUM SINTONG KECAMATAN TANAH PUTIH - Supiani '; Suarman '; Rina Selva Johan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of the problems in this study was the lack of students interest. This study was aimed to determine the increase in students interest in social subject class V Darul Ulum Islamic Elementary School Sintong Tanah Putih by using cooperative learning model Student Teams Achievement Division. This research was a classroom action research (CAR) was conducted in two cycles. Each cycle consists of two meetings. Subjects in this study the number of fifth grade students with 22 students consisting of 10 males and 12 females. Classroom action research in order to succeed, the researchers set the stage that action planning, action, observation and reflection. The instrument of colleecting the data was observation sheet, that teacher and student activity sheets observation interest in learning. Based on the results, it can be concluded that the application of cooperative learning model STAD (Student Teams Achievement Division) increase the interest students of class V Government Elementary School Darul Ulum Sintong Tanah Putih, evidenced by 1) Activities of teachers of the first cycle of the first meeting with the percentage of 54, 17% (Not Good) further increased in the second meeting a percentage of 75.0% (Good). In the second cycle in the first meeting with a percentage of 87.5% (Very Good) increased in the second meeting siklsu II becomes 95.83% (Very Good)., 2) Activities of students meeting the first cycle of the first meeting with a percentage of 46.21% (Not Good) increased at a second meeting be 65.15% (Good) further increased in the second cycle to the first dipertemuan increased to 82.6% (Very Good) increased to 91.67% (Very Good) in the second meeting of the second cycle, and 3) average the percentage of student interest at the first meeting reached 56.36% (Good), and then increased in the second meeting of the first cycle with an average percentage of 66.36% (Good). While on the second cycle, student interest increased to 75.45% (Good) and the second meeting of the second cycle reaches 84.55% (Very Good).Key Words: Cooperative Learning Model Type STAD, Students Interest, IPS